Does Fungal Chitosan Leave Noticeable Traces in Treated Wines? - Margot Paulin; Cécile Miot-Sertier; Julie Miranda; Amélie Vallet-Courbin; Julie Maupeu; Cédric Delattre; Joana Coulon; Virginie Moine; Axel Marchal; Stéphanie Roi; Thierry Doco; Marguerite Dols-Lafargue (Foods)
Background (1): The use of fungal chitosan as an antiseptic in wine appears as a promising alternative to sulfur dioxide for the elimination of Brettanomyces bruxellensis sensitive strains. Nevertheless, its utilization raises the question, “how are the treated wines different from the untreated ones?” Methods (2): Chitosan treatment residues were sought in the oligosaccharide and polysaccharide fractions and among 224 low MW ions (<1800 g·mol−1) in several wines by using liquid chromatography (size exclusion HPLC or LC-MS) and GC-MS. Standard oenological parameters were also examined as well as possible sensory modifications by a panel of tasters composed of experts and non-experts. Results (3): None of these methods enabled the reproducible and reliable identification of a treated wine without comparing it to its untreated control. The fingerprints of treatment are not reliably detectable by the analytical methods used in this study. However, the treated wines seem permanently protected against the development of chitosan-sensitive strains of B. bruxellensis. Conclusions (4): If chitosan treatment modifies the wine, the associated changes were not identified by the liquid chromatography method mentioned above and they were not perceived by most people in our taster panel. However, the expected antimicrobial action of chitosan was observed on B. bruxellensis sensitive strains and persisted at least one year. Tolerant strains were less affected by these persistent effects.